Monetary policy rules and economic fluctuations - Taufiq Carnegie Dawood (Proceedings of AICS - Social Sciences, 2017)
This paper found, for economies with high unhedged foreign borrowing, different monetary rules has produced differences in dynamics. In particular policy rules which place large weights on stability of the exchange rate, amplifies macroeconomic variables fluctuations. This underscores importance for caution of intervening in the exchange rate markets for economies with high percentage of unhedged foreign debt.